The Protective Effects of Sulforaphane on High-Fat Diet-Induced Obesity in Mice Through Browning of White Fat - Liu, Yaoli; Fu, Xiazhou; Chen, Zhiyong; Luo, Tingting; Zhu, Chunxia; Ji, Yaoting; Bian, Zhuan (Frontiers in Pharmacology, 2021)
Background: Sulforaphane (SFN), an isothiocyanate naturally occurring in cruciferous vegetables, is a potent indirect antioxidant and a promising agent for the control of metabolic disorder disease. SFN treatment could prevent diet-induced glucose intolerance in rats and inhibit adipogenesis. Strategies aimed at induction of brown adipose tissue (BAT) could be potentially useful way to against obesity. However, in vivo protective effect against obesity by browning white adipocyte has not been reported. In this study, we aimed at evaluation the efficacy of the SFN against the high-fat induced-obesity mice and investigating the potential mechanism. Methods: High-Fat Diet-induced obese female C57BL/6 mice were intraperitoneally injected with SFN (10 mg kg−1) daily. Six weeks later, intraperitoneal glucose tolerance test (IPGTT) and insulin tolerance test (ITT) were performed, and body weight change, body fat mass were measured. The expression of adipogenesis and browning genes in white adipose tissue (WAT) were determined by RT -qPCR and western blot technologies. Histological examination of the adipose tissue samples were carried out with HE staining method and immunofluorescence staining was performed. In vitro, C3H10T1/2 adipocytes were treated with SFN to investigate the direct effects of SFN on the expression of adipogenesis genes. Results: SFN reduced the size of fat cells and suppressed HFD-induced body weight gain in mice. SFN suppressed the expression of key genes in adipogenesis, inhibited lipid accumulation in C3H10T1/2 cells, increased the expression of brown adipocyte-specific markers and mitochondrial biogenesis in vivo and in vitro, and decreased cellular and mitochondrial oxidative stress. These results suggested that SFN, as a nutritional factor, has great potential in the treatment of obesity and metabolic syndrome by inducing the browning of white fat and promoting glucose metabolism. Conclusion: SFN could significantly decrease the fat mass, and improve glucose metabolism and increase insulin sensitivity of HFD-induced obese mice. The possible mechanism is to promote the browning of WAT and enhance the mitochondrial biogenesis in WAT. Our study provides an important experimental evidence for developing SFN as a potential anti-obesity and related diseases.